Task design to foster the competence in social decision making on mathematics education - Keiichi Nishimura; Chiharu Honda (Sociedad Española de Investigación en Educación Matemática, 2019)
As society continues to progress, it is becoming increasingly more important to mathematically deal with issues, take risks and uncertainty into account, clarify the grounds for participating in judgements or decision making, and make critical deliberations. This competence is defined as "decision making". We present the design of a task about saving more lives with automatic external defibrillators (AEDs) in order to foster this competency in mathematics lessons. In methodological terms, we use Lesson Study to carefully anticipate the process of students' finding and solving problems. We review the design from different viewpoints, such as "What times and how should all the students in the class study?" or "When and what kind of materials should be presented?"